Misplaced talent : a guide to making better people decisions - Ungemah, Joe, 1976- (Hoboken, NJ : Wiley, 2015)
"High-value talent management must be relevant to today's workplace Misplaced Talent takes a hard look at the cluttered field of Talent Management, and offers a clear guide to making better people decisions in any organization. Deliberately challenging practitioners to do more, this insightful discussion sorts through the tools and techniques developed over the last century to examine their true relevance to the modern workplace. You'll learn which activities show the greatest potential to improve the lives of employees and the organizations they work for, and identify which of your existing practices don't really add enough value to be worth the expenditure of time, money, and potentially lost talent. The author asks you to make up your own mind about which approaches work best for your own specific talent decisions, but provides the best theory and practice available today as a foundation upon which to formulate a more relevant strategy. In a world of big data, the potential to understand employees and react appropriately has never been greater. So why is Talent Management as an industry relying on outdated theory and practices? This book is a guide to bringing HR up to date, giving you the tools, techniques, and perspective you need to demonstrate more value to your organization. Adopt the tools and techniques most effective in today's workplace Identify and discard methods that don't add value to the organization Implement critical changes that can transform the HR function Make better people decisions based on psychology and research Fundamentally, not much has changed in what constitutes good people practice. Practitioners must demonstrate the value of Talent Management, but the solutions implemented often fall short of the rigor and discipline they deserve. Misplaced Talent provides the insight you need to refocus attention and engage your organization about the value of better people decisions"--
Motivated Employees Are Engaged EmployeesChanges in Motivation with Age and Generations; Restoring the Balance with Person-Environment Fit; Chapter 5. Employee Development; Psychological Contract; Assessment for Development; Developmental Challenges; Support Through Coaching and Mentoring; Moving Together or Apart; Chapter 6. Change; Breaking the Psychological Contract; Succession Planning; High Potentials and the Learning Agile; Driving Performance; Big Data and Monitoring Change; From a Balanced to a Transactional Contract; Conclusion; About the Author; Acknowledgments; Resources; Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Decision making; Personnel management; Decision making; Group decision making; Personnel management; Problem solving; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Decision making; Personnel management; Electronic books